Lenguaje de los negocios: XBRL en España como referente para el manejo de la información contable y financiera en Colombia (Revista cientifica In Vestigium Ire, 2016)
The language XBRL (extensible Business Reporting Language) has been created in 1998 by the book-keeper and American auditor Charles Hoffman, with the intention of simplifying the automation of the exchange of financial information, by means of the use of the language extensible XML Markup Language (Extensible Language of Brands). Therefore, the general adoption of the technology XBRL, will rest in order that the corporations and investors harvest the benefits of simplifying processes to publish financial reports and to take decisions of investment (Alfred Berkeley, Vice-president of Nasdaq), constituting a benefit for the network he informs of supply of financial information, allowing that the book-keepers, financial advisers, analysts and investors obtain information with rapidity, confidence and consistency, route Internet.In the world area a leading country in the exchange of documents XBRL, is Spain, only in the year 2011, the Spanish entities presented by means of this language, near 766.000 reports. Meanwhile in Colombia from the Law 1314 of 2009, it is found that the State will regulate the related thing to the report of information in the standard XBRL and the Technical Advice of the Public Accountancy, includes it inside the group of procedure proposed in Other Procedure of Information (ONI). Nevertheless, in the national area still his implementation is in an incipient phase.The written present tries to indicate the process of implementation of the language XBRL developed by Spain, as modal for the process of convergence initiated by Colombia, bearing in mind that the regulation of these two countries, they take as a common denominator to be nourished of the juridical tradition of the Roman law.
Keywords: XML; standardization; taxonomía; jurisdiction of Spain; Law 1314 of 2009; red Book; process of convergence